Penile traction therapy for Peyronie’s disease—what’s the evidence? - Usta, Mustafa Faruk (Transl Androl Urol, 2016)
Penile traction therapy (PTT) is a new therapeutic option for men with Peyronie’s disease (PD). However, it has a long history of use in other fields of medicine including bone, skin, skeletal muscle, and Dupuytren’s. Mechanotransduction, or gradual expansion of tissue by traction, leads to the formation of new collagen tissue by cellular proliferation. As a molecular result, continuous extension of the fibrous plaque causes significant increases in collagenase and metalloproteinases, and, ultimately, to fibrous plaque softening and extension. This hypothetical knowledge has been supported by recent well designed experimental studies. Furthermore, several clinical papers have provided promising results on the use of PTT in PD patients. It has been shown in some series that the use of PTT significantly increases flaccid and stretched penile lengths and results in significant penile curvature improvement when compared to baseline. Furthermore, the use of PTT concomitantly with either verapamil or interferon α-2b has also been shown to be an effective therapy. Additionally, the beneficial effect of PTT on penile length before or after penile surgery in men with corporal fibrosis has been described. Finally, as a minimally invasive alternative treatment option to penile augmentation surgery in men with dysmorphophobia, PTT use has shown promising results by several experts. Studies have shown that PTT provides an acceptable, minimally invasive method that can produce effective and durable lengthening of the penis in men complaining of a small/short penis. There are, however, several criticisms related to the designs of the reported studies, such as small sample size and selection bias. Well-designed studies with larger numbers of patients and longer follow-up periods are, however, needed to establish the true benefits of PTT.